What Do You Do When Things Go Right? The Intrapersonal and Interpersonal Benefits of Sharing Positive Events . [article]. - Gable, Shelly L.
Four studies examined the intrapersonal and interpersonal consequences of seeking out others when good things happen (i.e., capitalization). Two studies shows that communicating personal positive events with others was associated with increased daily positive affect and well-being, above and beyond the impact of the positive event itself and other daily . Moreover, when others were perceived to repond actively and constructively (and not passively or destructively) to capitalization attempts, the benefits were further enhanced. Two studies found that close relationships in which one's partner typically responds to capitalization attempts enthusiastically were associated with higher relationship well-being (e.G., intimacy, daily marital satisfaction). The results are discussed in terms of the theoretical and empirical importance of understanding how people "cope" with positive events, cultivate positive emotions, and enhance social bonds. -- (from the author)
Keywords: Psychology-Periodicals.